2020
DOI: 10.1186/s12885-020-06980-5
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood transfusion has distinct postsurgical oncologic impact on patients with different stage of hepatocellular carcinoma

Abstract: Background: The influence of perioperative blood transfusion (PBT) on postsurgical survival of patients with different stage of hepatocellular carcinoma (HCC) is not well clarified. This study aimed to evaluate the impact of PBT on survival outcomes of different stage of HCC patients. Methods: Consecutive patients who underwent liver resection for HCC between January 2009 and November 2015 were identified from an HCC prospective database in authors' center. The survival outcomes were compared between patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In the survival curve obtained after PSM, we could see that in the BCLC-A group, the survival prognosis of the PBT group was significantly worse than that of the nonPBT group, while in the BCLC-BC group, the survival curve of the PBT group was not statistically different from that of the nonPBT group. This is consistent with the conclusion of Chen et al ( 17 ), but our study focuses on rHCC patients and can provide better guidance for rHCC patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the survival curve obtained after PSM, we could see that in the BCLC-A group, the survival prognosis of the PBT group was significantly worse than that of the nonPBT group, while in the BCLC-BC group, the survival curve of the PBT group was not statistically different from that of the nonPBT group. This is consistent with the conclusion of Chen et al ( 17 ), but our study focuses on rHCC patients and can provide better guidance for rHCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…We also noted that patients in the PBT group had complex tumor presentation. Some researchers also believed that some tumor characteristics such as tumor size and related manifestations such as venous tumor thrombus were risk factors for blood transfusion and blood loss ( 17 , 20 , 32 ). At present, for the definition of blood loss and blood transfusion in clinical practice, it is controversial whether blood loss affects the prognosis of patients ( 17 , 33 ) andwhether the presence of rupture necessarily means that there is more blood loss, due to which a higher transfusion volume is not conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24] In the international scientific literature of reference, it is well understood how to identify the best surgical procedure by analyzing clear clinical outcomes both in the setting of hepatobiliary surgery and in liver transplantation. [25][26][27][28][29][30] Otherwise, LR is a valid therapeutic strategy for elderly patients, who cannot be referred to a transplant program because of the potential severe complications associated with transplantation. In contrast, ESLD may limit interventional options to HCC treatment, influence pharmacokinetics of anticancer drugs, and render patients susceptible to hepatotoxicity, adding a risk for morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the conclusions drawn based on the total cohort did not apply to an individual, as the patients had tumors of different stages. Previous studies on hepatocellular carcinoma showed PBT to have different impact on long-term survival in different tumor stages (11,12). However, the impact of PBT on long-term survival has not been studied in patients with different stages of pCCA.…”
Section: Introductionmentioning
confidence: 98%